2021
DOI: 10.1038/s41598-021-81112-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a toothpaste with microcrystalline hydroxyapatite on the occurrence of early childhood caries: a 1-year randomized clinical trial

Abstract: The aim of this trial was to determine whether a toothpaste with microcrystalline hydroxyapatite is not inferior to a fluoride toothpaste in prevention of caries in children. This double-blinded randomized control trial compared two toothpastes regarding the occurrence of caries lesions using International Caries Detection and Assessment System (ICDAS) ≥ code 1 on the primary dentition within 336 days. The test group used a fluoride-free hydroxyapatite toothpaste three times daily while control group used a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 67 publications
(149 reference statements)
5
65
0
Order By: Relevance
“…However, Chandran et al (2016) showed that the administration of microHA in osteoporotic rats did not provide a higher regeneration efficiency than the sham group [48]. This is also in line with clinical findings [49][50][51]. RCT by Schlagenhauf et al (2019) showed that daily use of microHA dentifrice on caries progression was not significantly different from 1400 ppm fluoride toothpaste [49].…”
Section: Hasupporting
confidence: 60%
“…However, Chandran et al (2016) showed that the administration of microHA in osteoporotic rats did not provide a higher regeneration efficiency than the sham group [48]. This is also in line with clinical findings [49][50][51]. RCT by Schlagenhauf et al (2019) showed that daily use of microHA dentifrice on caries progression was not significantly different from 1400 ppm fluoride toothpaste [49].…”
Section: Hasupporting
confidence: 60%
“…Previous clinical, in situ and in vitro studies have established hydroxyapatite crystals in toothpaste and mouthrinse to be as effective as fluoride in reducing tooth demineralization as well as promoting caries remineralization. 28,31,33,39,40 For this reason, the present study investigated and compared the effectiveness of a HAP-based toothpaste with that of a standard non-prescription toothpaste containing 1450 ppm fluoride (NaF) in preventing root dentin demineralization (root caries). The daily use of the toothpaste was simulated using a netdemineralization pH-cycling caries model (caries prevention or anticaries model).…”
Section: Discussionmentioning
confidence: 99%
“…This observation confirmed the reports of previous studies in which the non-inferiority of HAP to fluoride in prevention and remineralization of enamel caries was demonstrated in three clinical studies and a similar pH cycling study. 28,31,32,39 Two randomized controlled trial demonstrated the non-inferiority of 10% HAP toothpaste to 1400 ppm and 500 ppm fluoride toothpaste respectively, 28,39 while an in situ study reported non-inferiority of 10% HAP toothpaste to 500 ppm fluoride toothpaste. 31 The pH cycling study showed the non-inferiority of 15% HAP oral care gel to 12,500 ppm fluoride gel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ideal properties of a dentifrice include minimal abrasive effect, non-irritating, non-toxic, non-staining, protects against caries and biofilm formation, while being costeffective and readily available [21]. Many studies have been conducted to test the efficacy of HA, especially in enamel and dentine remineralisation, biofilm control, reducing dentine sensitivity, and tooth whitening [5,10,11,[22][23][24][25][26][27][28][29][30]. Currently, only a few reviews report on nanomaterial in oral care products or HA in dentistry which includes restorative, preventative, and regenerative applications [5,10,11,31,32].…”
Section: Introductionmentioning
confidence: 99%